2014
DOI: 10.5489/cuaj.1513
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between bladder wall thickness and lower urinary tract symptoms: Does bladder wall thickness change after alpha-blocker therapy with alfuzosin?

Abstract: Cite as: Can Urol Assoc J 2014;8(1-2):e26-9. http://dx.doi.org/10.5489/cuaj.1513 Published online January 14, 2014. AbstractIntroduction: We evaluate the association between lower urinary tract symptoms (LUTS) and bladder wall thickness (BWT) and investigate whether alfuzosin might improve BWT. Methods: We retrospectively reviewed the data of 164 patients with LUTS. Patients were divided into 2 groups according to BWT (Group 1: BWT ≤5 mm, n = 69; Group 2: BWT >5 mm, n = 95). Age, international prostate symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…BWT has been shown to improve with alpha‐blocker therapy, and negatively correlate with the responsiveness of alpha‐blockers. Similar to BWT, DWT has been found to correlate with BOOI and decrease in DWT after transurethral prostatectomy …”
Section: Discussionmentioning
confidence: 88%
“…BWT has been shown to improve with alpha‐blocker therapy, and negatively correlate with the responsiveness of alpha‐blockers. Similar to BWT, DWT has been found to correlate with BOOI and decrease in DWT after transurethral prostatectomy …”
Section: Discussionmentioning
confidence: 88%
“…Results for the >5 mm group are consistent with those from a similar study with tolterodine, where a significant BWT reduction was observed after 12 weeks versus placebo in patients with baseline BWT of >5 mm; however, no patients with BWT ≤5 mm were included in this study for comparison. Recent retrospective evaluation of BWT in men with LUTS included baseline BWT above and below 5 mm, and found BWT reductions from 6.8 to 4.6 mm in a patient subgroup treated with alfuzosin for 12 weeks. It remains unclear whether this result reflects a true effect of treatment on BWT in men, since only patients with baseline BWT >5 mm were treated with alfuzosin and included in this analysis, based on the pre‐treatment baseline BWT value of 6.8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Franco et al, moreover, noted a highly significant correlation between IPP and BOO and highlighted that the association of this parameter with BWT produced the best diagnostic accuracy . Some authors, furthermore, depicted BWT as a good predictor of the outcomes after medical/surgical treatment of LUTS/BPH …”
Section: Discussionmentioning
confidence: 99%